Blood Pressure Control Among Non-Hispanic Black Adults Is Lower Than Non-Hispanic White Adults Despite Similar Treatment With Antihypertensive Medication: NHANES 2013–2018. (5th April 2022) - Hayes, Donald K; Jackson, Sandra L; Li, Yanfeng; Wozniak, Gregory; Tsipas, Stavros; Hong, Yuling; Thompson-Paul, Angela M; Wall, Hilary K; Gillespie, Cathleen; Egan, Brent M; Ritchey, Matthew D; Loustalot, Fleetwood
Abstract: BACKGROUND: Controlled blood pressure can prevent or reduce adverse health outcomes. Social and structural determinants may contribute to the disparity that despite equivalent proportions on antihypertensive medication, non-Hispanic Black (Black) adults have lower blood pressure control and more cardiovascular events than non-Hispanic White (White) adults. METHODS: Data from 2013 to 2018 National Health and Nutrition Examination Survey were pooled to assess control among Black and White adults by antihypertensive medication use and selected characteristics using the 2017 American College of Cardiology/American Heart Association (ACC/AHA) Blood Pressure Guideline definition (systolic blood pressure <130 mm Hg and diastolic blood pressure <80 mm Hg) among 4, 739 adults. RESULTS: Among those treated with antihypertensive medication, an estimated 34.9% of Black and 45.0% of White adults had controlled blood pressure. Control was lower for Black and White adults among most subgroups of age, sex, education, insurance status, usual source of care, and poverty–income ratio. Black adults had higher use of diuretics (28.5%—Black adults vs. 23.5%—White adults) and calcium channel blockers (24.2%—Black adults vs. 14.7%—White adults) compared with White adults. Control among Black adults was lower than White adults across all medication classes including diuretics (36.1%—Black adults vs. 47.3%—White adults), calcium channel blockers (30.2%—Black adults vs. 40.1%—White adults), and number of medication classes used. CONCLUSIONS: Suboptimal blood pressure control rates and disparities warrant increased efforts to improve control, which could include addressing social and structural determinants along with emphasizing implementation of the 2017 ACC/AHA Blood Pressure Guideline into clinical practice. Graphical Abstract: